Penerapan Nilai Budaya Melayu Dalam Mewujudkan Reformasi Birokrasi Indonesia - Sobri, Kiagus Muhammad (Universitas Brawijaya, Indonesia, 2009)
As existing empirical from culture, hence analyze to bureaucracy performance can not only be comprehended by pursuant to approach only logical, structure and function, but also can be traced by through concepts giving all mind to aspect of related to the base of nature of human being mind. From side look into the many visible bureaucracy as a system will be depended to to all its: perpetrator of executor and target, that is those who execute the the system and also those who become its target. Therefore if it is later happened the